PENYANDANG DISABILITAS DALAM GEREJA - Sat Herry Sucahyo (Marturia, 2022)
AbstractAccording to Galtung, three forms of violence are direct violence, structural violence and cultural violence. The three forms of violence are interrelated with one another. Violence exists and occurs everywhere. including the church. The church, which has a foundation of love as its main law, is not free from violent behavior. People with disabilities in the church have the potential to be victims of violence. Therefore, Christ's action when he healed two blind people became an example for the church to be friendly to brothers and sisters with disabilities. Being a friendly church means being friendly to all, without categorizing any particular group. A friendly church is a church that brings peace.. Abstrak Tiga bentuk kekerasan menurut Galtung adalah kekerasan langsung, kekerasan struktural dan kekerasan kultural. Ketiga bentuk kekerasan tersebut saling berkaitan antara satu dengan yang lain. Kekerasan tersebut ada dan terjadi disemua tempat. Termasuk juga di gereja. Gereja yang memiliki dasar kasih sebagai hukum utamanya, ternyata tak terhindar dari perilaku-perilaku kekerasan. Penyandang disabilitas di gereja memiliki potensi sebagai korban kekerasan. Oleh karenanya tindakan Kristus ketika menyembuhkan dua orang buta menjadi teladan bagi gereja ramah terhadap saudara penyandang disabilitas. Menjadi gereja yang ramah memiliki arti ramah pada semua, tanpa mengkotak-kotakkan kelompok tertentu. Gereja yang ramah adalah gereja yang membawa perdamaian.